2021
DOI: 10.1155/2021/6621425
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of CO2 in Magnesite under High Pressure and High Temperature from Molecular Dynamics Simulations

Abstract: CO2 transports in the Earth’s interior play a crucial role in understanding the deep carbon cycle and the global climate changes. Currently, CO2 transports inside of the Earth under extreme condition of pressure and temperature have not been understood well. In this study, the molecular dynamics (MD) calculations were performed to study CO2 transports under different CO2 pressures in slit-like magnesite pores with different pore sizes at 350~2500 K and 3~50 GPa are presented. Diffusion of CO2 in magnesite was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In this system, iron carbide is the stable carbon-bearing phase in the shallow and lowermost lower mantle, while MgCO 3 may be the stable carbon-bearing phase through much of the lower mantle, depending on how much our observed reaction temperatures overshoot the phase boundary. Along a cold subducting slab geotherm, temperatures are sufficiently cold to prevent the exchange reaction from occurring, and our experiments suggest that MgCO 3 is stable in the subducting slab throughout the lower mantle. Additionally, we compared the MgCO 3 reaction directly to the CaCO 3 reaction (the purple line in Figure ).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…In this system, iron carbide is the stable carbon-bearing phase in the shallow and lowermost lower mantle, while MgCO 3 may be the stable carbon-bearing phase through much of the lower mantle, depending on how much our observed reaction temperatures overshoot the phase boundary. Along a cold subducting slab geotherm, temperatures are sufficiently cold to prevent the exchange reaction from occurring, and our experiments suggest that MgCO 3 is stable in the subducting slab throughout the lower mantle. Additionally, we compared the MgCO 3 reaction directly to the CaCO 3 reaction (the purple line in Figure ).…”
Section: Resultsmentioning
confidence: 62%
“…Carbon is depleted due to the diffusion of CO 2 across the reaction barrier to react with Fe 3 Si. Carbon is a highly mobile element, as evidenced by the experimentally measured fast diffusion of CO 2 through carbonates 54 and the high calculated diffusivities of carbon in silicate melts. 55 , 56 We concluded that CO 2 diffuses quickly through the carbonate material to react with Fe 3 Si at the reaction front, as shown in eq 3 .…”
Section: Resultsmentioning
confidence: 99%